Performance of cities in the metropolitan region of Rio de Janeiro in hospitalizations for Covid-19. SIVEP-Gripe based study (Research, Society and Development, 2021)
Introduction: the concern about the capacity of health care, mainly hospital, increases with the upsurge of the Covid-19 epidemic. Objective: to analyze SIVEP-Gripe data from 18 municipalities in the metropolitan region of Rio de Janeiro, of patients hospitalized for SARS in public and private hospitals. Methods: It is an ecological epidemiological study and a historical cohort with the cities and patients as units of analysis, from March to November 2020. Odds ratios were estimated for signs and symptoms, risk factors, whether public or private hospital, ICU admissions and deaths. Pearson’s chi-square test (p90% of its residents. At least 25% of hospitals, public and private, admitted only one patient, leading to learning difficulties. Public hospitals were more likely to have older patients, black or brown skin color, with dyspnea, respiratory distress and low oxygen saturation, liver disease and immunosuppression, conditions that are at greater risk for negative outcomes. The chance of a patient having been in an ICU in a public hospital is about half of the private hospital and the chance of death was about three times. These results indicate that patients admitted to public hospitals had a failed assistance from primary care, since they had more signs and symptoms pointing to a negative outcome, indicating a delay in hospitalization. Conclusion: the studied municipalities, except Niterói, are not prepared to support their residents in the Covid-19 pandemic. There was a discrepancy in the attendance of public and private hospitals, as well as failures in primary care leading to a greater risk of unfavorable results and a high number of deaths in public hospital units.